Fiscal consolidation programs and income inequality - Brinca, Pedro (2022)
We document a strong empirical relationship between higher income inequality and stronger recessive impacts of fiscal consolidation episodes across time and space. To explain this finding, we develop a life-cycle economy with uninsurable income risk. We calibrate our model to match key characteristics of several European economies, including inequality and fiscal structures, and study the effects of fiscal consolidation programs. In our model, higher income risk induces precautionary savings behavior, which decreases the proportion of credit-constrained agents in the economy. These agents have less elastic labor supply responses to fiscal consolidations, which explain the correlation with inequality in the data.